Digital Multimodal Composing: An Innovative Approach to Teaching English for Computer Science at STIKOM Tunas Bangsa - Fitri Fitri; Rizky Khairunnisa Sormin (Jurnal Manajemen, Pendidikan Dan Ilmu Komputer, 2026)
This research explores the implementation of Digital Multimodal Composing (DMC) as an innovative pedagogical approach in teaching English for Computer Science at STIKOM Tunas Bangsa. In the era of digital transformation and Merdeka Belajar curriculum, integrating multimodal literacy into English language learning is essential to enhance students’ communicative competence and digital skills. This research employs a mixed-method approach, combining quantitative data from students’ performance and qualitative data from interviews and classroom observations. The findings reveal that DMC significantly improves students’ engagement, creativity, and language proficiency, particularly in reading and writing skills relevant to computer science contexts. Furthermore, students demonstrate increased motivation and autonomy in learning through multimodal tasks such as digital storytelling, video presentations, and interactive media production. The study also identifies challenges including technological limitations and varying levels of digital literacy among students. However, these challenges are mitigated through collaborative learning and guided instruction. The research concludes that Digital Multimodal Composing is an effective and transformative approach for English for Computer Science, aligning with global educational trends and the Indonesian curriculum reform.